A kind of water-based ceramic slurry and its preparation method and application
Through the design of aqueous ceramic slurry, the problems of poor interface compatibility and high resistance of ceramic composite separators are solved, and the high cycle stability and rate performance of lithium-ion batteries are achieved, especially in high current density, which shows higher discharge Specific capacity.
Patent Information
- Application Number
- CN202310589769.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-24
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-05-24
AI Technical Summary
The existing ceramic composite separators have poor interfacial compatibility, powder loss problems and increased interface resistance, which affect the electrochemical performance and safety performance of lithium-ion batteries.
The aqueous ceramic slurry is used, including ceramic particles, bentonite, sodium carboxymethylcellulose, dispersants and active agents. By adjusting the components and process, the wetting performance, liquid absorption rate and thermal stability of the membrane are improved, and the interface resistance is reduced.
It achieves good interface compatibility, low resistance and high thermal stability of ceramic composite separators, improves the cycle stability and rate performance of lithium-ion batteries, and especially shows higher discharge specific capacity under high current density.
Smart Images

Figure BDA0004245102600000021 
Figure BDA0004245102600000041 
Figure BDA0004245102600000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of diaphragm materials, and specifically relates to a water-based ceramic slurry and a preparation method and application thereof. Background Art
[0002] As a key component of lithium-ion batteries, the performance of the diaphragm will directly affect the internal resistance, capacity, cycle performance and safety performance of the assembled battery. On the one hand, due to the poor affinity between the non-polar polyolefin diaphragm and the polar electrolyte, the interfacial resistance of the lithium-ion battery is relatively high. On the other hand, the traditional polyolefin diaphragm has the disadvantages of low melting point, strong thermal shrinkage and easy deformation. When it is close to the melting point, it is easy to melt and shrink, causing the battery to short-circuit and explode, which has a great impact on the safety performance of the battery.
[0003] At present, the prior art discloses a ceramic composite diaphragm, which can improve the thermal stability and mechanical strength of the polyolefin diaphragm and avoid diaphragm puncture causing battery short circuit. However, the following problems exist in its application: on the one hand, the interface compatibility of the ceramic composite diaphragm with organic and inorganic materials is poor, which often leads to powder loss problems in the ceramic composite diaphragm; on the other hand, the ceramic coating in the ceramic composite diaphragm increases the interface resistance between the diaphragm and the electrode material to a certain extent, affecting the electrochemical performance of the battery.
[0004] Therefore, in this field, there is an urgent need to develop a ceramic composite diaphragm having good interface compatibility, low resistance and thermal stability to solve the above problems. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a water-based ceramic slurry and a preparation method and application thereof. The water-based ceramic slurry provided by the present invention has good affinity with the base film, and the prepared diaphragm not only has good wettability and high liquid absorption rate for the electrolyte, but also has good thermal stability and low interface resistance.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides an aqueous ceramic slurry. Taking the total mass of the aqueous ceramic slurry as 100%, the aqueous ceramic slurry comprises the following raw materials:
[0008]
[0009] The present invention provides a water-based ceramic slurry of a specific composition, so that the water-based ceramic slurry has good affinity with the base film, and the prepared diaphragm not only has good wettability and high liquid absorption rate to the electrolyte, but also has good thermal stability and low interface resistance. Among them, the ceramic particles can not only improve the thermal stability of the prepared diaphragm, but also have a high specific surface energy, which can greatly improve the affinity of the water-based ceramic slurry with the base film, so that the diaphragm has stronger wettability and liquid absorption rate, reduces the battery interface impedance, and the assembled secondary battery can also show better cycle stability and rate performance. In addition, bentonite can play an anti-settling role to prevent the slurry from settling; the activator can activate the active ingredients in the ceramic particles, and the dispersant and the activator have a synergistic effect, which is conducive to ensuring the uniform dispersion of the ceramic particles in the aqueous slurry system.
[0010] Compared with traditional ceramic composite diaphragms, the diaphragm prepared by the aqueous ceramic slurry provided by the present invention has lower charge transfer resistance and excellent interface compatibility, so that the assembled lithium-ion batteries all show good rate performance and cycle performance, especially at high current density, so that the lithium-ion battery with the prepared ceramic composite diaphragm has the advantage of higher discharge specific capacity.
[0011] In the present invention, the content of the ceramic particles is 25-35%, for example, it can be 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, etc.
[0012] In the present invention, by adjusting the content of ceramic particles, the diaphragm can store more electrolyte to facilitate the transmission of lithium ions. If the content is too low, the spacing between the ceramic particles will be too large, making it difficult to support the diaphragm coating to resist thermal shrinkage. Otherwise, tiny bubbles will be generated in the slurry during the coating process, and the bubbles will absorb heat and burst in the subsequent drying process.
[0013] In the present invention, the content of bentonite is 0.2-2%, for example, it can be 0.2%, 0.3%, 0.5%, 0.8%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% and the like.
[0014] In the present invention, the content of sodium carboxymethyl cellulose is 1-10%, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc.
[0015] In the present invention, the content of the dispersant is 1-5%, for example, 1%, 2%, 3%, 4%, 5%, etc.
[0016] In the present invention, by adjusting the content of the dispersant, the dispersibility of the powder is improved and the medium surface is reduced. If the content is too low, the slurry will have a very high viscosity, resulting in extremely poor fluidity, which will seriously affect the quality of the ceramic slurry. Otherwise, the slurry will flocculate and the stability will deteriorate, resulting in the slurry becoming more and more viscous and thicker, and reducing the various properties of the original slurry.
[0017] In the present invention, the content of the active agent is 1-5%, for example, it can be 1%, 2%, 3%, 4%, 5%, etc.
[0018] In the present invention, by adjusting the content of the surfactant, the surface tension of the rubber is reduced, the interfacial activity is increased, and the penetration and diffusion of the slurry into the diaphragm are promoted and improved. If the content is too low, the slurry will agglomerate, and vice versa, it will cause excessive slurry foam that is difficult to eliminate.
[0019] In the present invention, the water content is 45-60%, for example, it can be 45%, 48%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60% and the like.
[0020] Preferably, based on the total mass of the aqueous ceramic slurry being 100%, the aqueous ceramic slurry comprises the following raw materials:
[0021]
[0022] Preferably, the ceramic particles include any one of silicon nitride, aluminum oxide, zirconium oxide or titanium dioxide, or a combination of at least two thereof.
[0023] Preferably, the crystal structure of the silicon nitride is β phase.
[0024] Preferably, the average particle size of the ceramic particles is 30-100 nm, for example, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc.
[0025] In the present invention, by regulating the average particle size of the ceramic particles, the diaphragm has a uniform porosity, which is beneficial for the diaphragm to store more electrolyte, provide more channels for lithium ion transportation, and facilitate the rapid migration of lithium ions during the charging and discharging process.
[0026] Preferably, the aqueous ceramic slurry further comprises a binder.
[0027] In the present invention, the addition of a binder has a thickening effect.
[0028] Preferably, the binder includes any one of polytetrafluoroethylene (PTFE), styrene-butadiene emulsion (SBR) or water-based polyacrylate (PAA) or a combination of at least two thereof.
[0029] Preferably, based on the total mass of the aqueous ceramic slurry being 100%, the mass percentage of the binder is 3-7%, for example, 3%, 4%, 5%, 6%, 7%, etc.
[0030] Preferably, the dispersant includes any one of ammonium acrylate, ethylene-vinyl acetate copolymer or polystyrene, or a combination of at least two thereof.
[0031] Preferably, the active agent includes any one of isomeric decanol polyoxyethylene ether, alkylphenol polyoxyethylene ether or polyoxyethylene ester, or a combination of at least two thereof.
[0032] Preferably, the aqueous ceramic slurry further comprises a defoaming agent.
[0033] In the present invention, the addition of the defoaming agent has the effect of preventing the generation of tiny bubbles when the membrane is painted.
[0034] Preferably, the defoaming agent includes any one of GPES defoaming agent, higher alcohol, tributyl phosphate or dimethyl silicone oil, or a combination of at least two thereof.
[0035] Preferably, based on the total mass of the aqueous ceramic slurry as 100%, the mass percentage of the defoaming agent is 2-4%, for example, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, etc.
[0036] Preferably, the viscosity of the aqueous ceramic slurry is 0.1-0.5 Pa·s, for example, it may be 0.1 Pa·s, 0.2 Pa·s, 0.3 Pa·s, 0.4 Pa·s, 0.5 Pa·s, etc.
[0037] Preferably, the solid content of the aqueous ceramic slurry is 60-80%, for example, 60%, 65%, 70%, 75%, 80%, etc.
[0038] In a second aspect, the present invention provides a method for preparing the aqueous ceramic slurry according to the first aspect, the method comprising the following steps:
[0039] Ceramic particles, bentonite, sodium carboxymethyl cellulose, a dispersant, an active agent and water are mixed according to the formula amount to obtain the water-based ceramic slurry.
[0040] Preferably, a binder and a defoamer may be added before the mixing.
[0041] Preferably, based on the total mass of the aqueous ceramic slurry being 100%, the mass percentage of the binder is 3-7%, for example, 3%, 4%, 5%, 6%, 7%, etc.
[0042] Preferably, based on the total mass of the aqueous ceramic slurry as 100%, the mass percentage of the defoaming agent is 2-4%, for example, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, etc.
[0043] Preferably, the specific process of mixing ceramic particles, bentonite, sodium carboxymethyl cellulose, a binder, a dispersant, an active agent, a defoamer and water according to the formula comprises the following steps:
[0044] (1) mixing sodium carboxymethyl cellulose and water to obtain a sodium carboxymethyl cellulose solution, and then mixing the sodium carboxymethyl cellulose solution with bentonite, water, a dispersant, an active agent and a defoamer to obtain a mixed slurry;
[0045] (2) Mixing the mixed slurry obtained in step (1) with ceramic particles and a binder to obtain the aqueous ceramic slurry.
[0046] In a third aspect, the present invention provides an aqueous ceramic diaphragm, comprising a base membrane and an aqueous ceramic layer disposed on at least one side of the base membrane, wherein the aqueous ceramic layer is prepared from the aqueous ceramic slurry according to the first aspect.
[0047] Preferably, the thickness of the aqueous ceramic layer is 8-12 μm, for example, 8 μm, 8.2 μm, 8.5 μm, 8.8 μm, 9 μm, 9.2 μm, 9.5 μm, 9.8 μm, 10 μm, 10.2 μm, 10.5 μm, 10.8 μm, 11 μm, 11.2 μm, 11.5 μm, 11.8 μm, or 12 μm.
[0048] In the present invention, by adjusting the thickness of the water-based ceramic layer, the silicon nitride particles are dispersed and densely arranged on the surface of the base film under the action of the binder. The interface bonding force between the silicon nitride coating and the base film is strong, so that the spacing between the silicon nitride particles is reduced, and the coating that serves as a skeleton to support the diaphragm resists thermal shrinkage.
[0049] Preferably, the base film comprises a polyethylene base film and / or a polypropylene base film.
[0050] Preferably, the base film has a thickness of 16 μm-20 μm, for example, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, etc.
[0051] In a fourth aspect, the present invention provides a method for preparing the water-based ceramic diaphragm according to the third aspect, the method comprising the following steps:
[0052] The base film is immersed in the aqueous ceramic slurry described in the first aspect, and the aqueous ceramic diaphragm is obtained after drying.
[0053] As a preferred technical solution of the present invention, the method comprises the following steps:
[0054] First, the base film is pre-dried to remove moisture. The specific pre-drying conditions are drying at 80-110°C for 1 hour. Then, the pre-dried base film is immersed in the slurry for 2-15 minutes until there is basically no bubble escape. After drying, the water-based ceramic diaphragm is obtained.
[0055] In a fifth aspect, the present invention provides a secondary battery, comprising a positive electrode, a negative electrode, an electrolyte and a separator, wherein the separator is the aqueous ceramic separator according to the third aspect.
[0056] Compared with the prior art, the present invention has the following beneficial effects:
[0057] The present invention provides an aqueous ceramic slurry, which has good affinity with a base film, and the prepared diaphragm not only has good wettability and high liquid absorption rate to the electrolyte, but also has good thermal stability and low interface resistance. Among them, the ceramic particles can not only improve the thermal stability of the prepared diaphragm, but also have a high specific surface energy, which can greatly improve the affinity of the aqueous ceramic slurry and the base film, so that the diaphragm has stronger wettability and liquid absorption rate, reduces the battery interface impedance, and the assembled secondary battery can also show better cycle stability and rate performance. In addition, bentonite can play an anti-settling role to prevent the slurry from settling; the activator can activate the active ingredients in the ceramic particles, and the dispersant and the activator have a synergistic effect, which is conducive to ensuring the uniform dispersion of the ceramic particles in the aqueous slurry system. DETAILED DESCRIPTION
[0058] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0059] Example 1
[0060] This embodiment provides an aqueous ceramic slurry. Taking the total mass of the aqueous ceramic slurry as 100%, the aqueous ceramic slurry includes the following raw materials:
[0061]
[0062] The average particle size of the β-phase silicon nitride is 65 nm, the viscosity of the water-based ceramic slurry is 0.3 Pa·s, and the solid content is 70%.
[0063] This embodiment provides a method for preparing the above-mentioned water-based ceramic slurry, which comprises the following steps:
[0064] (1) mixing sodium carboxymethyl cellulose and water once to obtain a sodium carboxymethyl cellulose solution, and then mixing the sodium carboxymethyl cellulose solution with bentonite, water, an ammonium acrylate dispersant, an isomeric decanol polyoxyethylene ether active agent, and a GPES defoamer to obtain a mixed slurry;
[0065] (2) The mixed slurry obtained in step (1) is stirred with β-phase silicon nitride at a speed of 500 r / min for 2 hours, and then stirred with a polytetrafluoroethylene binder at a speed of 600 r / min for 5 hours to obtain the water-based ceramic slurry.
[0066] Example 2
[0067] This embodiment provides an aqueous ceramic slurry. Taking the total mass of the aqueous ceramic slurry as 100%, the aqueous ceramic slurry includes the following raw materials:
[0068]
[0069]
[0070] The average particle size of the β-phase silicon nitride is 65 nm, the viscosity of the water-based ceramic slurry is 0.3 Pa·s, and the solid content is 70%.
[0071] This embodiment provides a method for preparing the above-mentioned water-based ceramic slurry, which comprises the following steps:
[0072] (1) mixing sodium carboxymethyl cellulose and water to obtain a sodium carboxymethyl cellulose solution, and then mixing the sodium carboxymethyl cellulose solution with bentonite, water, an ammonium acrylate dispersant, an alkylphenol polyoxyethylene ether active agent, and a higher alcohol defoamer to obtain a mixed slurry;
[0073] (2) The mixed slurry obtained in step (1) is stirred with β-phase silicon nitride at a speed of 500 r / min for 2 hours, and then stirred with a styrene-butadiene emulsion binder at a speed of 600 r / min for 5 hours to obtain the water-based ceramic slurry.
[0074] Example 3
[0075] This embodiment provides an aqueous ceramic slurry. Taking the total mass of the aqueous ceramic slurry as 100%, the aqueous ceramic slurry includes the following raw materials:
[0076]
[0077]
[0078] The average particle size of the β-phase silicon nitride is 65 nm, the viscosity of the water-based ceramic slurry is 0.3 Pa·s, and the solid content is 70%.
[0079] This embodiment provides a method for preparing the above-mentioned water-based ceramic slurry, which comprises the following steps:
[0080] (1) mixing sodium carboxymethyl cellulose and water to obtain a sodium carboxymethyl cellulose solution, and then mixing the sodium carboxymethyl cellulose solution with bentonite, water, an ammonium acrylate dispersant, a polyoxyethylene ester active agent, and a tributyl phosphate defoamer to obtain a mixed slurry;
[0081] (2) The mixed slurry obtained in step (1) is stirred with β-phase silicon nitride at a speed of 500 r / min for 2 hours, and then stirred with a water-based polyacrylate binder at a speed of 600 r / min for 5 hours to obtain the water-based ceramic slurry.
[0082] Example 4
[0083] The difference between this embodiment and embodiment 1 is that the viscosity of the aqueous ceramic slurry is 0.05 Pa·s, and the rest is the same as embodiment 1.
[0084] Example 5
[0085] The difference between this embodiment and embodiment 1 is that the viscosity of the aqueous ceramic slurry is 1 Pa·s, and the rest is the same as embodiment 1.
[0086] Example 6
[0087] The difference between this embodiment and embodiment 1 is that the solid content of the aqueous ceramic slurry is 50%, and the rest is the same as embodiment 1.
[0088] Example 7
[0089] The difference between this embodiment and embodiment 1 is that the solid content of the aqueous ceramic slurry is 90%, and the rest is the same as embodiment 1.
[0090] Comparative Example 1
[0091] The difference between this comparative example and Example 1 is that, based on the total mass of the aqueous ceramic slurry being 100%, the mass percentage of β-phase silicon nitride is 10%, and the water content is adaptively adjusted so that the content of the aqueous ceramic slurry system is 100%. The rest is the same as Example 1.
[0092] Comparative Example 2
[0093] The difference between this comparative example and Example 1 is that, based on the total mass of the aqueous ceramic slurry being 100%, the mass percentage of β-phase silicon nitride is 40%, the water content is adaptively adjusted so that the content of the aqueous ceramic slurry system is 100%, and the rest is the same as Example 1.
[0094] Comparative Example 3
[0095] The difference between this comparative example and Example 1 is that the ammonium acrylate dispersant is replaced with an equal amount of isomeric decanol polyoxyethylene ether active agent, and the rest is the same as Example 1.
[0096] Comparative Example 4
[0097] The difference between this comparative example and Example 1 is that the isomeric decanol polyoxyethylene ether active agent is replaced by an equal content of an ammonium acrylate dispersant, and the rest is the same as Example 1.
[0098] Comparative Example 5
[0099] The difference between this comparative example and Example 1 is that, based on the total mass of the aqueous ceramic slurry being 100%, the mass percentage of the ammonium acrylate dispersant is 0.1%, and the mass percentage of the isomeric decanol polyoxyethylene ether active agent is 5.9%, and the rest are the same as Example 1.
[0100] Comparative Example 6
[0101] The difference between this comparative example and Example 1 is that, based on the total mass of the aqueous ceramic slurry being 100%, the mass percentage of the ammonium acrylate dispersant is 5.9%, and the mass percentage of the isomeric decanol polyoxyethylene ether active agent is 0.1%, and the rest are the same as Example 1.
[0102] Application Examples 1 to 7 and Comparative Application Examples 1 to 6
[0103] The aqueous ceramic slurries provided in Examples 1 to 7 and Comparative Examples 1 to 6 are used to prepare aqueous ceramic diaphragms, and the preparation method is as follows:
[0104] First, the base film is dried at 100°C for 1 hour, and the pre-dried base film is cooled to below 60°C, and then the pre-dried base film is immersed in an aqueous ceramic slurry for 15 minutes until there is basically no bubble escape, and the immersed membrane is hung in an electric heated blast drying oven at 50°C to dry the surface moisture, and then placed in a vacuum drying oven at 80°C for 24 hours to dry out the moisture in the pores to obtain the aqueous ceramic membrane.
[0105] The prepared waterborne ceramic diaphragm is assembled into a lithium ion half-cell, and the preparation method is as follows:
[0106] Manganese iron lithium, Super P conductive agent and polyvinylidene fluoride binder are mixed with an appropriate amount of N-methylpyrrolidone in a mass ratio of 95:3:2, and then evenly applied on aluminum foil, placed in a vacuum oven at 180°C for 8 hours, and a pole piece with a diameter of 10 mm is prepared using a slicer, which is assembled into a manganese iron lithium half-cell with the above-mentioned diaphragm and lithium metal sheet.
[0107] Test conditions
[0108] The water-based ceramic diaphragms provided in Application Examples 1 to 7 and Comparative Application Examples 1 to 6 were tested, and the test method was as follows:
[0109] (1) Heat shrinkage rate: Stack the diaphragm into 3 layers, flatten them, exhaust the air between the films, take out the cutting plate (20×20), cut out the diaphragm sample, and measure the diameter A of the cut sample. 1 , set the oven temperature to 150℃, keep it warm for 1 hour after reaching the temperature. Put the sample in the oven and keep it warm for 2 hours.
[0110] Use a stopwatch or the oven's built-in timer to time. After 2 hours, remove the diaphragm and cool for 10 minutes before measuring the sample's diameter A. 2 , diaphragm heat shrinkage
[0111] =(A 1 -A 2 ) / A 1 ×100%;
[0112] (2) Porosity: The sample is first loaded and recorded as M 0 . Place it in a clean beaker and add water until it is submerged. Next, place the beaker directly in the drying oven and heat it until it boils.
[0113] The boiling state needs to be maintained for two hours until the water completely penetrates the air in the electrode, then stop heating and lower the temperature in the room. Take out the sample and put it in a small hanging basket, put it on the hook, and the sample should be submerged in water. Then weigh it again, and count it as M 1 Take out the sample, wipe off all the moisture on the surface, and weigh it again. The weight at this time is recorded as M 2 . Diaphragm porosity = (M 2 -M 0 ) / (M 2 -M 1 )×100%;
[0114] (3) Liquid absorption rate: The sample is first loaded and recorded as M 0 , put it into a beaker with electrolyte, let it stand for 30 minutes, take out the sample, weigh it, and record it as M 1 , membrane liquid absorption rate = (M1 -M 0 ) / M 0 ×100%;
[0115] (4) Impedance: The ordinary diaphragm and the ceramic modified diaphragm were assembled into button cells and subjected to EIS testing.
[0116] The lithium ion half-cells provided in Application Examples 1 to 7 and Comparative Application Examples 1 to 6 were subjected to cycle performance tests, and the test method was as follows:
[0117] At 45°C, the lithium-ion battery is charged at a constant current of 0.5C (nominal capacity) to a voltage of 4.2V, then charged at a constant voltage of 4.2V to a current ≤ 0.05C, and after standing for 10 minutes, discharged at a constant current of 3C to a cut-off voltage of 2.5V. The above is one charge and discharge cycle. The lithium-ion battery is charged and discharged 1000 times at 45°C under the above conditions. Among them, the capacity retention rate is calculated according to the following formula.
[0118]
[0119] The test results are shown in Table 1:
[0120] Table 1
[0121]
[0122]
[0123] It can be seen from Table 1 that the water-based ceramic diaphragms prepared in Application Examples 1-3 provided by the present invention can maintain a good state, among which the ceramic diaphragm provided in Application Example 1 has the best performance, and the corresponding half-cell also has relatively good cycle performance.
[0124] Compared with Application Example 1, Application Example 4 reduces the viscosity of the aqueous ceramic slurry, and the resulting modified ceramic diaphragm has excessively high thermal shrinkage and porosity, and has relatively large impedance, which affects the service life of the battery.
[0125] Compared with Application Example 1, Application Example 5 increases the viscosity of the aqueous ceramic slurry too much, making the slurry thicker and thicker, which will cause flocculation and deteriorate the stability of the slurry, thereby affecting the performance of the modified ceramic diaphragm and reducing the service life of the battery.
[0126] Compared with Application Example 1, Application Example 6 has a too low solid content, which results in a significant decrease in the thermal stability of the modified ceramic diaphragm, thereby reducing the safety performance of the battery, and further causing the impedance of the prepared battery to be high, affecting the cycle performance of the battery.
[0127] Compared with Application Example 1, Application Example 7 has a higher solid content, which makes the over-curing phenomenon more obvious, resulting in edge scattering effect of the ceramic slurry, affecting its liquid absorption rate and impedance, and reducing the battery cycle performance.
[0128] The difference between Comparative Application Example 1 and Application Example 1 is that, based on the total mass of the aqueous ceramic slurry being 100%, the mass percentage of β-phase silicon nitride is 10%. There are too few ceramic particles, resulting in excessive spacing between the ceramic particles, making it difficult to support the coating of the diaphragm to resist thermal shrinkage. Therefore, the thermal shrinkage rate is extremely large, affecting the high-temperature cycle characteristics of the battery.
[0129] The difference between Comparative Application Example 2 and Application Example 1 is that, based on the total mass of the aqueous ceramic slurry being 100%, the mass percentage of β-phase silicon nitride is 40%. There are too many ceramic particles, which causes tiny bubbles to be generated during the slurry coating process. The bubbles absorb heat and rupture during the subsequent drying process. Therefore, the porosity is too large, resulting in excessive impedance, which affects the battery life and makes it difficult to apply to actual production.
[0130] Comparative Application Examples 3 and 5 show that the content of the dispersant exceeds the preferred range of the present invention, resulting in flocculation of the slurry, poor stability, and increasing viscosity of the slurry, thereby affecting the service life of the battery.
[0131] Comparative Application Examples 4 and 6 show that when the content of the active agent is too low, the slurry will agglomerate, and when the content is too high, the slurry will have excessive foam that is difficult to eliminate, making it difficult for the slurry to diffuse and penetrate into the diaphragm, resulting in low interfacial activity of the diaphragm and excessively high surface tension, which affects the impedance and cycle performance of the battery.
[0132] Comparative Application Examples 3 and 4 show that there is a synergistic effect between the ammonium acrylate dispersant and the isomeric decanol polyoxyethylene ether active agent.
[0133] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A water-based ceramic slurry, characterized in that: Taking the total mass of the aqueous ceramic slurry as 100%, the aqueous ceramic slurry includes the following raw materials: Wherein, the active agent includes any one or a combination of at least two of isomeric decanol polyoxyethylene ether, alkylphenol polyoxyethylene ether or polyoxyethylene ester; The dispersant includes ammonium acrylate.
2. The aqueous ceramic slurry according to claim 1, characterized in that Taking the total mass of the aqueous ceramic slurry as 100%, the aqueous ceramic slurry includes the following raw materials:
3. The aqueous ceramic slurry according to claim 1, characterized in that The ceramic particles include any one of silicon nitride, aluminum oxide, zirconium oxide or titanium dioxide, or a combination of at least two of them.
4. The aqueous ceramic slurry according to claim 3, characterized in that The crystal structure of the silicon nitride is β phase.
5. The aqueous ceramic slurry according to claim 1, characterized in that: The average particle size of the ceramic particles is 30-100 nm.
6. The aqueous ceramic slurry according to claim 1, characterized in that: The aqueous ceramic slurry also includes a binder.
7. The aqueous ceramic slurry according to claim 6, characterized in that: The binder includes any one of polytetrafluoroethylene, styrene-butadiene emulsion or water-based polyacrylate or a combination of at least two of them.
8. The aqueous ceramic slurry according to claim 6, characterized in that: Based on the total mass of the aqueous ceramic slurry being 100%, the mass percentage of the binder is 3-7%.
9. The aqueous ceramic slurry according to claim 1, characterized in that: The aqueous ceramic slurry also includes a defoaming agent.
10. The aqueous ceramic slurry according to claim 9, characterized in that: The defoaming agent includes any one of GPES defoaming agent, higher alcohol, tributyl phosphate or dimethyl silicone oil, or a combination of at least two thereof.
11. The aqueous ceramic slurry according to claim 9, characterized in that: Based on the total mass of the aqueous ceramic slurry being 100%, the mass percentage of the defoaming agent is 2-4%.
12. The aqueous ceramic slurry according to claim 1, characterized in that: The viscosity of the aqueous ceramic slurry is 0.1-0.5 Pa·s.
13. The aqueous ceramic slurry according to claim 1, characterized in that: The solid content of the aqueous ceramic slurry is 60-80%.
14. A method for preparing the aqueous ceramic slurry according to any one of claims 1 to 13, characterized in that: The method comprises the following steps: Ceramic particles, bentonite, sodium carboxymethyl cellulose, a dispersant, an active agent and water are mixed according to the formula amount to obtain the water-based ceramic slurry.
15. The method according to claim 14, characterized in that A binder and a defoamer may also be added before the mixing.
16. The method according to claim 15, characterized in that Based on the total mass of the aqueous ceramic slurry being 100%, the mass percentage of the binder is 3-7%.
17. The method according to claim 15, characterized in that Based on the total mass of the aqueous ceramic slurry being 100%, the mass percentage of the defoaming agent is 2-4%.
18. The method according to claim 15, characterized in that The specific process of mixing ceramic particles, bentonite, sodium carboxymethyl cellulose, a binder, a dispersant, an active agent, a defoamer and water according to the formula comprises the following steps: (1) mixing sodium carboxymethyl cellulose and water to obtain a sodium carboxymethyl cellulose solution, and then mixing the sodium carboxymethyl cellulose solution with bentonite, water, a dispersant, an active agent and a defoamer to obtain a mixed slurry; (2) Mixing the mixed slurry obtained in step (1) with ceramic particles and a binder to obtain the aqueous ceramic slurry.
19. A water-based ceramic diaphragm, characterized in that: The aqueous ceramic diaphragm comprises a base membrane and an aqueous ceramic layer arranged on at least one side of the base membrane, and the aqueous ceramic layer is prepared from the aqueous ceramic slurry according to any one of claims 1-13.
20. The water-based ceramic diaphragm according to claim 19, characterized in that: The thickness of the aqueous ceramic layer is 8 μm-12 μm.
21. The water-based ceramic diaphragm according to claim 19, characterized in that: The base film includes a polyethylene base film and / or a polypropylene base film.
22. The water-based ceramic diaphragm according to claim 19, characterized in that: The base film has a thickness of 16 μm-20 μm.
23. A method for preparing the water-based ceramic diaphragm according to any one of claims 19 to 22, characterized in that: The method comprises the following steps: The base film is immersed in the aqueous ceramic slurry according to any one of claims 1 to 13, and the aqueous ceramic diaphragm is obtained after drying.
24. A secondary battery, characterized in that: The secondary battery comprises a positive electrode, a negative electrode, an electrolyte and a separator, and the separator is the aqueous ceramic separator according to any one of claims 19 to 22.